Exploring sonographer emotional well-being: NHS sonographers' experience of the restorative function of professional supervision. (May 2023) - Carr, Ryan; White, Helen
Introduction: Following recommendations of the Francis report (2013), healthcare professional groups have formalised restorative supervision within practice in order to maintain emotional well-being among staff and provide quality of care for patients. There is a scarcity of research available on how professional supervision is utilised as a restorative device within current practice for sonographers. Methodology: An online cross-sectional, descriptive survey was used to gain qualitative details and nominal data on sonographer experiences of professional supervision. Themes were developed through thematic analysis. Results: A total of 56% of participants did not identify professional supervision as part of their current practice; 50% of participants felt emotionally unsupported within their work. The majority felt 'unsure' of how professional supervision would affect their working day; however, they highlighted that a restorative function would be valued equally as professional development functions of practice. The barriers to professional supervision as a restorative function demonstrate that an understanding of what sonographer needs are should be considered in approaches to professional supervision. Conclusion: This study found that participants identify professional supervision in its formative and normative functions more commonly than its restorative functions. It also found that sonographers are found wanting of emotional support, with 50% of sonographers feeling unsupported and identifying a restorative supervision need to their working practice. Implications for practice: The need to establish a system that supports the emotional well-being of sonographers is highlighted. This should help with retention of sonographers in a career where burnout is evidenced.